A Bubble‐Mediated Intelligent Microscale Electrochemical Device for Single‐Step Quantitative Bioassays. (14th April 2014) - Yang, Fan; Zuo, Xiaolei; Li, Zhenhua; Deng, Wangping; Shi, Jiye; Zhang, Guojun; Huang, Qing; Song, Shiping; Fan, Chunhai
<x xml:space="preserve">Abstract</x> An intelligent microscale electrochemical device (iMED) for one‐step, quantitative and multiplexed electrochemical detection of biomarkers for infectious diseases and tumors is developed. A "plug‐in‐cartridge" technology is introduced and adapted for use in screen‐printed electrodes (SPEs) in electrochemical devices. Using this iMED, biomarkers for two types of tumors and one infectious disease are detected at sub‐ng/mL levels in less than 30 min. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>